2008
DOI: 10.1111/j.1600-0714.2008.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum cytokine and T regulatory cell levels in patients with burning mouth syndrome

Abstract: IL-2 and TNF-alpha might play a role in burning mouth syndrome. Burning mouth syndrome may occur as a sign of predisposition to autoimmunity. Presence of low levels of CD28(+) supports the provision that BMS might be a pre-autoimmune disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
69
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 41 publications
2
69
1
Order By: Relevance
“…Accordingly, we found that BMS patients present an increase in total protein and IL-6, and a decrease in TNF-α in comparison with controls. Another study also reported a decrease in serum TNF-α levels in this group [29], but yet others showed no significant differences between patients and controls regarding levels of salivary TNF-α [30,31]. Interestingly, BMS patients subjected to salivary stimulation therapy demonstrated a significant reduction of symptoms in parallel with a decrease in the salivary levels of total protein and an increase in TNF-α [32].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, we found that BMS patients present an increase in total protein and IL-6, and a decrease in TNF-α in comparison with controls. Another study also reported a decrease in serum TNF-α levels in this group [29], but yet others showed no significant differences between patients and controls regarding levels of salivary TNF-α [30,31]. Interestingly, BMS patients subjected to salivary stimulation therapy demonstrated a significant reduction of symptoms in parallel with a decrease in the salivary levels of total protein and an increase in TNF-α [32].…”
Section: Discussionmentioning
confidence: 99%
“…The main symptoms of BMS are pain/discomfort in the tongue, palate, and gums and taste disturbance. [6][7][8][9][10][11][12] BMS is associated with psychological conditions such as depression, hypochondria, and cancer phobia. It predominantly affects women after menopause 3,4 and is believed to be associated with hormone withdrawal in some patients.…”
mentioning
confidence: 99%
“…5 BMS is diagnosed after exclusion of organic pathologies (eg, xerostomia, lichen planus, and allergy to dental materials) that manifest similar signs and symptoms. 6,7,[18][19][20][21][22][23] The essential immunoendocrine profile of BMS, for example, activation of innate and acquired immune system and cellular and humoral immunity, we attempted to identify factors associated with BMS by comparing BMS patients and controls. [6][7][8][9][10][11][12] BMS is associated with psychological conditions such as depression, hypochondria, and cancer phobia.…”
mentioning
confidence: 99%
“…65 Then, salivary stimulation therapy may increase levels of TNF-α that are reduced in the serum of these patients. 66 In fact, TNF-α clearly induces the production of caspases (or cysteine-aspartic proteases or cysteine-dependent aspartate-directed proteases) involved in apoptosis signaling pathways. 67 TNF-α is also an important neuroinflammatory molecule involved in the mechanism of pain and is crucial in the pathways of neuropathic pain at peripheral and central levels.…”
Section: Nonpharmacological Therapeutic Strategiesmentioning
confidence: 99%